FFS‐mode OS‐LCD for reducing eye strain. Issue 10 (7th January 2014) - Hatsumi, Ryo; Fukai, Shuji; Kubota, Yusuke; Yamashita, Akio; Jikumaru, Mika; Baba, Haruyuki; Moriya, Koji; Kubota, Daisuke; Kusunoki, Koji; Hirakata, Yoshiharu; Koyama, Jun; Yamazaki, Shunpei; et al.
Abstract In order to reduce eye strain, a driving method for reducing flickers of liquid crystal display (LCD) is devised. For this driving, an oxide semiconductor (OS) is used in a backplane, liquid crystal and alignment layer materials are optimized, and a fringe field switching (FFS) mode with a structurally formed storage capacitor is used. This work reveals that suitable usages of positive and negative liquid crystals differ from each other according to their characteristics. This work also describes an OS‐LCD with a touch sensor we fabricated for mobile devices, which proves the possibility of reducing‐eye‐strain technology (REST) with reduced flickers.